Revitalization Strategy of Agricultural Financing Through Facilitating Agricultural Financing Activities by FPPS in West Lombok Regency - Zaenafi Ariani (International Consortium of Education and Culture Research Studies, 2020)
The common problem for farmers is that it does not have good access to financing institutions, so it is difficult to obtain credit or farmer business financing, such as People's Business Credit (KUR) from banking. Directorate General of Agricultural facilities and means in TA. The 2019 is carrying out activities of smallholders financing facilitator (FPPS) aimed at facilitating farmers in the access of financing/capital. The role and function of FPPS is to bridge farmers in conducting access to the banking, so that the revitalization of agricultural financing is achieved where the Government has provided various financing facilities to the farmers to develop their land ventures. As the first step of the implementation of FPPS activities, Ditjen PSP CQ Directorate of Agricultural Financing has implemented the material supply for the prospective energy FPPS in TA. 2017. The supply is intended for FPPS energy to have skills and knowledge about the procedure to see the potential of farmer's business, as well as to facilitate the financing from the Bank or other financing sources.